2022
DOI: 10.1111/plb.13399
|View full text |Cite
|
Sign up to set email alerts
|

The 2018 hot drought pushed conifer wood formation to the limit of its plasticity: Consequences for woody biomass production and tree ring structure

Abstract: Hot droughts are expected to increase in Europe and disturb forest ecosystem functioning. Wood formation of trees has the potential to adapt to those events by compensatory mechanisms between the rates and durations of tracheid differentiation to form the typical pattern of vital wood anatomical structures.• We monitored xylogenesis and measured wood anatomy of mature silver fir (Abies alba Mill.) and Scots pine (Pinus sylvestris L.) trees along an elevational gradient in the Black Forest during the hot drough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 112 publications
1
8
0
Order By: Relevance
“…Also, in 2018 we detected higher resistance of trw of silver fir in comparison to Norway spruce, but we could not substantiate these findings for d or rbi. In addition, d of Norway spruce and silver xylem cell differentiation processes and reduced woody biomass production in the study region during 2018 (Larysch et al, 2021(Larysch et al, , 2022. In agreement with previous findings with respect to the 2003 drought (Vitali et al, 2017), we could also substantiate higher drought resistance of d, trw, and rbi of silver fir in 2018 with increasing elevation.…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…Also, in 2018 we detected higher resistance of trw of silver fir in comparison to Norway spruce, but we could not substantiate these findings for d or rbi. In addition, d of Norway spruce and silver xylem cell differentiation processes and reduced woody biomass production in the study region during 2018 (Larysch et al, 2021(Larysch et al, , 2022. In agreement with previous findings with respect to the 2003 drought (Vitali et al, 2017), we could also substantiate higher drought resistance of d, trw, and rbi of silver fir in 2018 with increasing elevation.…”
Section: Figuresupporting
confidence: 92%
“…Besides the fact that resistance indices of trw and rbi of Norway spruce were the lowest in both drought years, the lower resistance of d and mxd of spruce in 2018 compared to 2003 indicates that resource availability for latewood production was considerably compromised by the multiple stressors of cone production, water deficit, depleted carbohydrate reserves and increased respiratory demands during the extreme summer drought of 2018 (Teskey et al, 2015;Hacket-Pain et al, 2017;Arend et al, 2021). Previous studies have shown that the rate of cell wall thickening of conifers was significantly reduced during periods of intra-seasonal drought, but endogenous control can potentially compensate reduced cell differentiation rates by prolonging their duration (Balducci et al, 2016;Stangler et al, 2021;Larysch et al, 2022). We hypothesize that such compensatory mechanisms became ineffective during latewood formation of 2018 and that drought stress in late summer and autumn might have caused a premature cessation of xylem cell differentiation phases (Gruber et al, 2010;Saderi et al, 2019;Larysch et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…In this special issue, a broad range of observational and experimental studies are provided that relate to tree health, drought and heat stress resistance and recovery at multiple levels, including causes and consequences of drought-induced tree mortality. The studies use a wealth of approaches, covering remote sensing West et al 2022), ground-based monitoring (Frei et al 2022;George et al 2022), different management regimes (Bose et al 2021;Meyer et al 2022), including species mixture effects Santamarina et al 2022), field studies on wood formation plasticity (Larysch et al 2022), acclimation potential at the leaf level (Weithmann et al 2021;Petrik et al 2022) and recovery potential at the tree level (Kn€ uver et al 2022). These are supported by field- (Guan et al 2022;Kahmen et al 2022;Kn€ uver et al 2022) and lab-based (Kunert et al 2021;Petruzzellis et al 2021;McAdam et al 2022) ecophysiological studies that will increase our understanding of the impacts and consequences of global change-type droughts.…”
mentioning
confidence: 99%
“…2021 ; Larysch et al . 2022; Meyer et al . 2022), impacts of different management regimes (Bose et al .…”
mentioning
confidence: 99%
“…This special issue, edited by Schuldt & Ruehr (2022), evaluates tree and forest responses to the 2018 European hot drought, one of the most severe droughts ever recorded in Central Europe. It illustrates and differentiates viewpoints across scales, from acclimation potential and regulatory mechanisms at the leaf level (Kunert et al 2021;Weithmann et al 2021;McAdam et al 2022;Petrik et al 2022), embolism and wood formation plasticity (Petruzzellis et al 2021;Larysch et al 2022;Meyer et al 2022), impacts of different management regimes (Bose et al 2021;Meyer et al 2022) and species interaction effects in mixtures Santamarina et al 2022), to results from remote sensing West et al 2022).…”
mentioning
confidence: 99%